Evaluation of silver nanoparticle toxicity in vivo skin and in vitro keratinocytes [in press] - Samberg, Meghan E.; Oldenburg, Steven J.; Monteiro-Riviere, Nancy A. (Environmental Health Perspectives, 2009)
"Introduction: Products utilizing the antimicrobial properties of silver nanoparticles (Ag-nps) may be found in health and consumer products that routinely contact skin. Objectives: The study was designed to assess the potential cytotoxicity of Ag-nps in human epidermal keratinocytes (HEK), and their inflammatory and penetrating potential into porcine skin in vivo. Materials and Methods: Eight different Ag-nps were used in this study. HEK viability was assessed by MTT, alamarBlue (aB), and CellTiter 96Aqueous One (96AQ); release of proinflammatory mediators IL-1b, IL-6, IL-8, IL-10, and TNF-a were measured. Skin was dosed topically for 14 consecutive days. Results: The effect of the unwashed Ag-nps on HEK viability after 24 h exposure indicated a significant dose-dependent decrease (p<0.05) at 0.34mg/ml with aB and 96AQ and at 1.7mg/ml with MTT. However, both the washed Ag-nps and carbon-coated Ag-nps showed no significant decrease in viability at any concentration assessed by any of the three assays For each of the unwashed Ag-nps a significant increase (p<0.05) in concentration IL-1b, IL-6, IL-8, and TNF-a was noted. Localization of all Ag-nps was depicted in cytoplasmic vacuoles of HEK. Macroscopic observations showed no gross irritation in porcine skin, while microscopic and ultrastructural observations showed areas of focal inflammation and localization of Ag-nps on the surface and in the upper stratum corneum layers of the skin. Conclusion: This study provides a better understanding Ag-nps safety in vitro as well as in vivo and a basis for occupational and risk assessment. Ag-nps are non-toxic when dosed in washed Ag-nps solutions or carbon-coated."